2004
DOI: 10.1177/153537020422900207
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Receptor-Deficient MMTV-TGF-α/Leprdb Leprdb Female Mice Do Not Develop Oncogene-Induced Mammary Tumors

Abstract: Being overweight is a risk factor for postmenopausal breast cancer and is associated with an increased incidence and shortened latency of spontaneous and chemically induced mammary tumors in rodents. However, leptin-deficient obese Lep(ob)Lep(ob) female mice have reduced incidences of spontaneous and oncogene-induced mammary tumors. Of interest, leptin enhances the proliferation of human breast cancer cell lines in which leptin receptors are expressed, which suggests that leptin signaling plays a role in tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(99 citation statements)
references
References 67 publications
1
96
0
2
Order By: Relevance
“…Leptin has been implicated as a growth-promoting factor for Brca [1]. Animal studies also support a role for leptin in mammary tumor development as evidenced by the fact that mice deficient in leptin, Lep ob Lep ob [4], or with non-functioning leptin receptors, Lepr db Lepr db [5], did not develop transgene-induced mammary tumors. It is possible that the levels of adiponectin and leptin receptors, as well as the balance of serum adiponectin and leptin, are critical factors in mammary tumorigenesis.…”
mentioning
confidence: 69%
“…Leptin has been implicated as a growth-promoting factor for Brca [1]. Animal studies also support a role for leptin in mammary tumor development as evidenced by the fact that mice deficient in leptin, Lep ob Lep ob [4], or with non-functioning leptin receptors, Lepr db Lepr db [5], did not develop transgene-induced mammary tumors. It is possible that the levels of adiponectin and leptin receptors, as well as the balance of serum adiponectin and leptin, are critical factors in mammary tumorigenesis.…”
mentioning
confidence: 69%
“…[46][47][48] Furthermore, we have reported that genetically obese leptin-(Lep) and leptin High fat diet and MT latency MP Cleary et al receptor-(Lepr) deficient mice crossbred with MMTV-TGF-a mice did not develop MTs. 24,25 Although we did not determine serum leptin levels in the present study, it has been reported that serum leptin levels were highest in obesity-prone rats compared to obesity-resistant and control rats, while obesity-resistant rats had higher leptin levels than the control rats. 49 In a second study, comparing only high fat fed animals, obesity-prone rats had higher plasma leptin than did obesity-resistant rats.…”
Section: Discussionmentioning
confidence: 93%
“…23 When followed to 24 months of age MT incidence was increased to at least 50%. 24,25 Here we describe the effect on body weight and MT development while feeding normally lean MMTV-TGF-a female mice a moderately high fat diet from 10 until 85 weeks of age.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, addition of leptin to MCF-7 breast cancer cells decreases the expression of the cancer suppression protein p53, exploiting cancer cell survival property [40]. In a female transgenic mouse model susceptible to mammary tumor growth, deficiency of either the leptin gene (ob/ob) [41] or its receptor (db/db) resulted in no development of mammary tumors, whereas tumors were detected in over half of the controls [42].…”
Section: Leptinmentioning
confidence: 99%